ECONOMIC AND NON-ECONOMIC IMPLICATIONS OF COMMUNITY BASED TOURISM (CBT) SUPPLY CHAIN AT AROUND TELUK KILUAN BEACH TANGGAMUS REGENCY LAMPUNG PROVINCE OF INDONESIA - Aida, Neli; Suman, Agus; Sakti, Rachmad Kresna; ., Susilo (International Journal of Supply Chain Management, 2019)
Community-based tourism is a form of participatory tourism management, aimed at reviewing the application of the principles of Community Based Tourism (CBT) supply chain in tourism development on Teluk Kiluan Beach and knowing its implications for the welfare of the surrounding community. This study uses a qualitative approach at Teluk Kiluan Tanggamus Beach research site in Lampung Province, and conducts primary data collection with interviews, in-depth interviews, and observations from key informants and other supporting informants then as a validity test. The results of the study show that CBT in developing coastal tourism on Teluk Kiluan applies economic principles and non-economic principles (social, cultural, political and institutional). The economic dimension of the implications of CBT supply chain on the welfare of the communities around the Gulf coast is characterized by: absorption of local labor, development of business units, doubling of people's income, and growing and developing new investors. Improving education, quality of life, changes in social values, freedom of action, environmental sustainability and the involvement of institutional strengths are the implications of implementing CBT on non-economic welfare of the community.